生命的咏叹调 ：探讨林黛玉以花为题的诗词 = The Aria of life : a discussion of Lin Dai-yu’s poems on flora - 黄美馨 Ng, Meixin (2009)
本文运用弗洛伊德理论中的爱欲和死欲概念，对《红楼梦》中林黛玉前八十回以花为题的诗词作品进行分析讨论。笔者将探讨《葬花吟》和《桃花行》两首长篇诗词，和黛玉题帕诗三首、菊花诗三首和《唐多令•咏絮》这些短篇诗词。笔者在此文中主要把黛玉视作一个人，而不是一个小说人物，以便能更好地通过心理分析概念，探讨黛玉的无意识世界中爱欲与死欲的纠葛，而从中展现黛玉面对生命所表现的积极态度。笔者从爱欲和死欲的角度，结合黛玉诗词里的意象和黛玉作诗时的语境，发现黛玉的诗词中有一些反复出现的主题，例如对花草的爱惜、对爱情的憧憬、对死亡的抗拒、对自我的眷恋等，都是爱欲的表现。因此，我们能从黛玉的诗词中窥视其爱欲的活动，和死欲在她身上的频频挫败。既然黛玉的无意识世界主要由爱欲主宰，那么，我们可以见证黛玉顽强的生命力。她拒绝向重病屈服、不愿向爱情的阻力低头。黛玉的身上闪烁着积极灿烂的生命光辉。或许，这也是林黛玉形象在历史与文学的浪潮中历久不衰的原因之一。This essay will analyse the poems, specifically, those that adopt flora as their main imagery, that Lin Dai-yu composed in the first 80 Chapters of the “Dream of the Red Mansion”, using the constructs of “Eros” and “death instinct”, which are put forth by Sigmund Freud. The long poems “zang hua yin” (the song of burying flowers) and “tao hua xing” (poem to eulogize peach blossoms) will be critiqued, as well as various short poems such as “daiyu ti pa shi” (the three poems that Dai-yu wrote on the handkerchief given to her by Bao-yu), “juhua shi” (the three poems extolling chrysanthemum), and “tang duo ling, yong xu” (the poem singing praises of cotton). The approach taken in this essay will be to view Dai-yu as a person, instead of a fictitious character, so as to apply the psychoanalytical tools to her, in the hope of uncovering the struggles of Eros and the death instinct in her unconscious mind. Through this approach, the essay will establish that Dai-yu holds a zealous outlook on life.Taking the literary imageries and contexts of the creation of the poems into consideration, a few recurring themes emerge, such as the love she shows towards flora, her longing for love, her dread of death, her narcissism etc. These are all manifestations of Eros. Hence, the poems of Dai-yu show us the activity of Eros, and the repeated suppression of the death instinct in her. Since Dai-yu’s unconscious world is governed by Eros, we can say that she has a tenacious pool of vitality. She concedes defeat to neither illness nor obstacles in love. We see the enthusiasm that Dai-yu has towards life. Perhaps, this is one of the reasons that Dai-yu is not forgotten in the endless waves of history and literature over the years.